2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25640
|View full text |Cite
|
Sign up to set email alerts
|

In Their Shoes: Student Perspectives on the Connection between Empathy and Engineering

Abstract: interests include developing pedagogical strategies to improve STEM students' ethical reasoning skills; exploring the role of empathy within design, innovation and sustainability; synthesizing the influence of societal and individual worldviews on decision-making; assessing STEM students' learning in the spaces of design, ethics, and sustainability; and exploring the impact of pre-engineering curriculum on students' abilities and career trajectories.c American Society for Engineering Education, 2016 In Their S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…For example, prior work that examined media portrayals of engineering (Sochacka et al 2014) found that engineering is mainly presented as using math and science to problem-solve, which can create in students a cognitive dissonance when learning about the importance of empathic skills in engineering (Walther et al 2020). This cognitive dissonance can cause students to be conflicted about how to be engineers because empathy is not objective, logical, or rational and, therefore, not considered engineering work (Fila and Hess 2016;Walther et al 2020). Because of the beliefs that students hold about who engineers are and what they need to do in a given situation, even when they learn about considering others when designing, they might still end up choosing to provide a technical-centered solution rather than a solution that fits the needs of others (von Unold et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, prior work that examined media portrayals of engineering (Sochacka et al 2014) found that engineering is mainly presented as using math and science to problem-solve, which can create in students a cognitive dissonance when learning about the importance of empathic skills in engineering (Walther et al 2020). This cognitive dissonance can cause students to be conflicted about how to be engineers because empathy is not objective, logical, or rational and, therefore, not considered engineering work (Fila and Hess 2016;Walther et al 2020). Because of the beliefs that students hold about who engineers are and what they need to do in a given situation, even when they learn about considering others when designing, they might still end up choosing to provide a technical-centered solution rather than a solution that fits the needs of others (von Unold et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Grace, who mentioned that she wanted to pursue a career towards customer services, also said, 'because of the career I'm going into … , you kinda really have to,' which does not acknowledge how empathy plays a broader role to support consideration of the impact of engineering decisions at the societal level. Previous studies in engineering have already found that the recognition of empathy is sometimes perceived as an add-on (Strobel et al 2013), depending on the 'scope' of the project (Fila and Hess 2016) or sometimes not even counted as part of problem solving (Brewer et al 2017). The belief that empathy is only relevant in certain contexts can establish risk where students constrain the impact of their decisions to the macro-level.…”
Section: Discussionmentioning
confidence: 99%
“…Stephan and Finlay described how empathy training might unintentionally lead to a broadened gap between groups that one perceives as distinct. 62 Likewise, Walther et al discussed how engineering students might perceive empathy as something outside of engineering practice, 8 a similar finding elucidated from student interviews conducted by Fila and Hess 88 . Our suggestion is to use active pedagogies.…”
Section: Closing Discussionmentioning
confidence: 85%
“…Others have found that engineering students tend to exhibit empathy throughout the design process [29][30][31]; thus, we postulate that empathy frameworks -such as Walther et al's [32] model of empathy in engineering or empathic design frameworks, such as the principles listed by Mattelmaki et al [11] -can provide a useful heuristic for considering variations in how empathy manifests in design and how to support empathy in developmentally appropriate ways.…”
Section: Identifying Developmentally Appropriate Learning Goalsmentioning
confidence: 84%